Lessons from the canine Oxtr gene: populations, variants and functional aspects. (14th December 2016) - Bence, M.; Marx, P.; Szantai, E.; Kubinyi, E.; Ronai, Z.; Banlaki, Z.
Abstract : Oxytocin receptor (OXTR) acts as a key behavioral modulator of the central nervous system, affecting social behavior, stress, affiliation and cognitive functions. Variants of the Oxtr gene are known to influence behavior both in animals and humans; however, canine Oxtr polymorphisms are less characterized in terms of possible relevance to function, selection criteria in breeding and domestication. In this report, we provide a detailed characterization of common variants of the canine Oxtr gene. In particular (1) novel polymorphisms were identified by direct sequencing of wolf and dog samples, (2) allelic distributions and pairwise linkage disequilibrium patterns of several canine populations were compared, (3) neighbor joining (NJ) tree based on common single nucleotide polymorphisms (SNPs) was constructed, (4) mRNA expression features were assessed, (5) a novel splice variant was detected and (6) in vitro functional assays were performed. Results indicate marked differences regarding Oxtr variations between purebred dogs of different breeds, free‐ranging dog populations, wolf subspecies and golden jackals. This, together with existence of explicitly dog‐specific alleles and data obtained from the NJ tree implies that Oxtr could indeed have been a target gene during domestication and selection for human preferred aspects of temperament and social behavior. This assumption is further supported by the present observations on gene expression patterns within the brain and luciferase reporter experiments, providing a molecular level link between certain canine Oxtr polymorphisms and differences in nervous system function and behavior. Abstract : Neighbor‐joining tree supports the hypothesis that Oxtr variants could have been a selection target during canine domestication.